The value of nature : ecological politics in India - Kotahri,Smitu(Editor) Imtiaz Ahmed(Editor) Reifeld,Helmut(Editor) (Rainbow Publishers, 2003)
Contributed papers presented at a workshop held during March 6-9, 2002.